The effect of gel structure on the in vitro digestibility of wheat starch-Mesona chinensis polysaccharide gels. Issue 1 (14th December 2018) - Yuris, Anynda; Goh, Kelvin Kim Tha; Hardacre, Allan Keith; Matia-Merino, Lara
Abstract : The digestibility of wheat starch gels in the presence of Mesona chinensis polysaccharide (MCP) was studied. Abstract : The digestibility of wheat starch gels in the presence of Mesona chinensis polysaccharide (MCP) was studied. MCP was found to be the most effective polysaccharide in reducing wheat starch digestion in comparison to starch gels of similar hardness containing xanthan, guar, locust bean gum (LBG) and agar. A 33% reduction in the digestibility of intact starch gels containing 5% w/w MCP (after 120 minutes of digestion) was observed and this was attributed to the strengthening of the gels in the presence of high concentration of the polysaccharide. In contrast, despite a reduction in the firmness of the gel when 2% w/w MCP was present, there was a 7% reduction in starch digestibility and hence, firmness was deduced to be not solely responsible for the digestibility of the gels. When these gels were macerated, starch digestibility was reduced regardless of the MCP concentration. Starch digestion in the macerated samples seemed to cease after 10 minutes with about 30% more starch remaining when 5% w/w MCP was present, suggesting that the amount of starch available for digestion was reduced in the presence of MCP. The reduced availability of starch for digestion was hypothesised to be due to starch-MCP interactions, which formed amylose-MCP complexes that are likely to be resistant to enzymatic digestion. Overall, this work shows the potential for MCP to be utilized as an ingredient to reduce the glycaemic index.